Penyuluhan Profesi Keinsinyuran dan Demo IoT Melalui Webinar kepada Siswa/Siswi SMK Muhammadiyah 02 Tangerang Selatan - Adi Setiawan; Sri Yatmani; Herbert Rajagukguk; Novy Hapsari (Jurnal Pendidikan dan Pembelajaran, 2022)
To introduce young people at school at early stage to engineering profession, an activity such as giving a lecture and some demo to them becomes important. This activity will hopefully create better understanding on engineering world especially in the field of electrical engineering by introducing an increasingly popular technology called IoT (Internet of Things). The target school is SMK Muhammadiyah 02 Tangerang Selatan. Because of COVID-19 pandemic situation and PSBB rules implemented in Tangerang Selatan in which school students had to study from home, then the lecture was given online by Zoom application on Tuesday, August 18th at 13.30 – 15.00 WIB. The partcipants attending the online lecture reached 26 consisting of grade III students of Computer Network program and some teachers as well. The results of the questionnaires given shortly before the webinar ends show that for Introduction of Engineering Profession, the majority of them (61,54%) states Interesting Enough, for Introduction of IoT the majority (57,69%) says Interesting and for IoT Demo the majority (53,85%) thinks Interesting Enough. The benefit of this webinar is clear when the majority of participants (57,69%) agrees Beneficial to them and all of them (100%) say Agree that this activity is also introduced to other students at school